Combinatorial Analysis - 26.11 Integer Partitions: Compositions

From testwiki
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
26.11.E2 c m ⁑ ( 0 ) = Ξ΄ 0 , m number-of-compositions-C-into-parts π‘š 0 Kronecker 0 π‘š {\displaystyle{\displaystyle c_{m}\left(0\right)=\delta_{0,m}}}
\ncompositions[m]@{0} = \Kroneckerdelta{0}{m}

numbcomp(0, m) = KroneckerDelta[0, m]
Error
Error Missing Macro Error - -
26.11.E3 c m ⁑ ( n ) = ( n - 1 m - 1 ) number-of-compositions-C-into-parts π‘š 𝑛 binomial 𝑛 1 π‘š 1 {\displaystyle{\displaystyle c_{m}\left(n\right)=\genfrac{(}{)}{0.0pt}{}{n-1}{% m-1}}}
\ncompositions[m]@{n} = \binom{n-1}{m-1}

numbcomp(n, m) = binomial(n - 1,m - 1)
Error
Error Missing Macro Error - -
26.11.E4 βˆ‘ n = 0 ∞ c m ⁑ ( n ) ⁒ q n = q m ( 1 - q ) m superscript subscript 𝑛 0 number-of-compositions-C-into-parts π‘š 𝑛 superscript π‘ž 𝑛 superscript π‘ž π‘š superscript 1 π‘ž π‘š {\displaystyle{\displaystyle\sum_{n=0}^{\infty}c_{m}\left(n\right)q^{n}=\frac{% q^{m}}{(1-q)^{m}}}}
\sum_{n=0}^{\infty}\ncompositions[m]@{n}q^{n} = \frac{q^{m}}{(1-q)^{m}}

sum(numbcomp(n, m)*(q)^(n), n = 0..infinity) = ((q)^(m))/((1 - q)^(m))
Error
Error Missing Macro Error - -
26.11#Ex1 F 0 = 0 subscript 𝐹 0 0 {\displaystyle{\displaystyle F_{0}=0}}
F_{0} = 0

F[0] = 0
Subscript[F, 0] == 0
Skipped - no semantic math Skipped - no semantic math - -
26.11#Ex2 F 1 = 1 subscript 𝐹 1 1 {\displaystyle{\displaystyle F_{1}=1}}
F_{1} = 1

F[1] = 1
Subscript[F, 1] == 1
Skipped - no semantic math Skipped - no semantic math - -
26.11#Ex3 F n = F n - 1 + F n - 2 subscript 𝐹 𝑛 subscript 𝐹 𝑛 1 subscript 𝐹 𝑛 2 {\displaystyle{\displaystyle F_{n}=F_{n-1}+F_{n-2}}}
F_{n} = F_{n-1}+F_{n-2}
n β‰₯ 2 𝑛 2 {\displaystyle{\displaystyle n\geq 2}}
F[n] = F[n - 1]+ F[n - 2]
Subscript[F, n] == Subscript[F, n - 1]+ Subscript[F, n - 2]
Skipped - no semantic math Skipped - no semantic math - -
26.11.E7 F n = ( 1 + 5 ) n - ( 1 - 5 ) n 2 n ⁒ 5 subscript 𝐹 𝑛 superscript 1 5 𝑛 superscript 1 5 𝑛 superscript 2 𝑛 5 {\displaystyle{\displaystyle F_{n}=\frac{(1+\sqrt{5})^{n}-(1-\sqrt{5})^{n}}{2^% {n}\,\sqrt{5}}}}
F_{n} = \frac{(1+\sqrt{5})^{n}-(1-\sqrt{5})^{n}}{2^{n}\,\sqrt{5}}

F[n] = ((1 +sqrt(5))^(n)-(1 -sqrt(5))^(n))/((2)^(n)*sqrt(5))
Subscript[F, n] == Divide[(1 +Sqrt[5])^(n)-(1 -Sqrt[5])^(n),(2)^(n)*Sqrt[5]]
Skipped - no semantic math Skipped - no semantic math - -